Marxist theory of dependence and overexploitation of workforce: History and current debate in Latin America - de Moraes, Isaías A. [UNESP]; de Almeida, Hugo M.V. [UNESP] (Instituto de Investigaciones Dr. Jose Maria Luis Mora, 2020)
The article lists as a unit of analysis the Marxist Theory of Dependency that emerged in the 1960s in Latin America. This paper seeks to shed light on the past, but primarily to fill some gaps in the contributions of this theory, especially in relation to the concept of Overexploitation of the Workforce to the contemporary economy. To reach its objective, the article used the historical-bibliographic-analytical methodology and prioritized as technical procedures a systematic approach through the critical evaluation of the bibliographic data on the subject. The article is divided into two sections: the first section presents the main readings and propositions of the precursor theorists of the Marxist Theory of Dependency; in the second section, the text focused on presenting how this theory is being reborn in Latin America and how the studies on the Overexploitation of the Workforce are becoming in an interesting tool of economic analysis.
Teoria marxista da dependência e superexploração da força de trabalho: História e debate atual na América Latina
Keywords: Economic imperialism; Latin American economic thought; Marxist Theory of Dependency; Overexploitation of the workforce; Unequal exchange